Analisis Konsumsi Daging Sapi Di Provinsi Papua Barat - T.W. Widayati; S. Widodo; Masyhuri Masyhuri; A. Suryantini (Universitas Andalas, 2011)
The study aims to determine the level of beef consumption and the factors that influence the consumption of beef in West Papua. The data used in this study are monthly time series data of BPS, sourced from all districts in the province of West Papua from 1990 to 2004. Data were analyzed by using multiple linear regression equation by Ordinary Least Square method. The results showed that the average beef consumption per capita per year for people of West Papua is 0.79 kg. The increasing of population and income per capita affected the increasing of beef consumption significantly. Increasing the price of chicken meat, pork prices and the price of rice has significant effect of reducing domestic consumption of beef. Increasing the price of tuna, squid and sweet potatoes have a significant effect in increasing of the domestic consumption of beef.